2021
DOI: 10.2174/1570159x19666210225154835
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteases and Chemokines in Neurotrauma: New Targets for Immune Modulating Therapeutics in Spinal Cord Injury

Abstract: : Progressive neurological damage after brain or spinal cord trauma causes loss of motor function and treatment is very limited. Clotting and hemorrhage occur early after spinal cord (SCI) and traumatic brain injury (TBI), inducing aggressive immune cell activation and progressive neuronal damage. Thrombotic and thrombolytic proteases have direct effects on neurons and glia, both healing and also damaging, bidirectional immune cell interactions. Serine proteases in the thrombolytic cascade, tissue- and urokina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 180 publications
0
5
0
Order By: Relevance
“…The severe, destructive, and persistent inflammatory response after spinal cord injury can exacerbate local tissue damage and lead to the development of syringomyelia, characterized by the infiltration of phagocytic macrophages at the injury site. In recent years, there has been a growing emphasis on understanding the immune microenvironment after spinal cord injury, leading to the exploration of various immunotherapeutic approaches for spinal cord injury repair, demonstrating promising therapeutic prospects [ [24] , [25] , [26] ]. The efficacy of therapeutic interventions for spinal cord injury (SCI) often fall below expectations, primarily due to factors such as the diverse immune microenvironment following SCI, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The severe, destructive, and persistent inflammatory response after spinal cord injury can exacerbate local tissue damage and lead to the development of syringomyelia, characterized by the infiltration of phagocytic macrophages at the injury site. In recent years, there has been a growing emphasis on understanding the immune microenvironment after spinal cord injury, leading to the exploration of various immunotherapeutic approaches for spinal cord injury repair, demonstrating promising therapeutic prospects [ [24] , [25] , [26] ]. The efficacy of therapeutic interventions for spinal cord injury (SCI) often fall below expectations, primarily due to factors such as the diverse immune microenvironment following SCI, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the amino acid sequence inserted between the first two CC amino acids in the sequence, there are four categories of chemokines: C, CC, CXC, and CX3C. CC chemokines are associated with the activation and migration of monocytes and lymphocytes, whereas CXC chemokines are often linked to the activation and migration of neutrophils and macrophages [ 73 ]. After SCI, the CC chemokine subtype CCL2 is protective by recruiting macrophages to the site of the injury and promoting the conversion of macrophages into an anti-inflammatory, neuroprotective M2 phenotype.…”
Section: Molecular Mechanisms In the Nervous Systemmentioning
confidence: 99%
“…Mosaic serine proteases have diversified effects on SCI. There is protective effect on increasing neuron and glial cell proliferation and migration by tissue-type plasminogen activator (tPA) [ 8 , 10 ], as well as damaging effect on apoptosis and activating inflammatory and immune response by thrombin [ 11 ]. Serine protease neuropsin and protease M/neuros expressed by oligodendrocyte upregulate after SCI, and promote demyelination [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serine protease neuropsin and protease M/neuros expressed by oligodendrocyte upregulate after SCI, and promote demyelination [ 12 ]. Thrombin, a widely studied serine protease targeted by nafamostat, is a multifunctional enzyme that is restricted from the CNS under physiological conditions [ 11 ]. Recent research has shown that it has a crucial role in traumatic brain injury (TBI), SCI, neurodegenerative diseases (Alzheimer's and Parkinson's diseases) and ischemic stroke [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%